2018
DOI: 10.1139/bcb-2017-0274
|View full text |Cite
|
Sign up to set email alerts
|

Emerging branches of the N-end rule pathways are revealing the sequence complexities of N-termini dependent protein degradation

Abstract: The N-end rule links the identity of the N-terminal amino acid of a protein to its in vivo half life as some N-terminal residues confer metabolic instability to a protein via their recognition by the cellular machinery that targets them for degradation. Since its discovery, the N-end rule has generally been defined as set of rules of whether an N-terminal residue is stabilizing or not.However, recent studies are revealing that the N-terminal code of amino acids conferring protein instability is more complex th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 73 publications
(60 reference statements)
1
15
0
Order By: Relevance
“…In agreement with these results, even a partial ablation of the Arg/N-degron pathway sensitizes cells to apoptosis (55). In sum, the Arg/N-degron pathway is a regulator of apoptosis, acting largely (but not necessarily exclusively) (34) as an antiapoptotic circuit (55). By destroying proapoptotic Ct-fragments, the Arg/N-degron pathway contributes to thresholds that prevent a transient or otherwise weak proapoptotic signal from reaching the point of commitment to apoptosis.…”
Section: Accelerators Of Apoptosis As Arg/n-degron Substratessupporting
confidence: 68%
See 1 more Smart Citation
“…In agreement with these results, even a partial ablation of the Arg/N-degron pathway sensitizes cells to apoptosis (55). In sum, the Arg/N-degron pathway is a regulator of apoptosis, acting largely (but not necessarily exclusively) (34) as an antiapoptotic circuit (55). By destroying proapoptotic Ct-fragments, the Arg/N-degron pathway contributes to thresholds that prevent a transient or otherwise weak proapoptotic signal from reaching the point of commitment to apoptosis.…”
Section: Accelerators Of Apoptosis As Arg/n-degron Substratessupporting
confidence: 68%
“…1 and 2 and SI Appendix, Fig. S2A) (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Other studies, in the 1990s and afterward, have also identified many internal degrons, defined as degradation signals whose functionally essential elements do not include either Nt-residues or C-terminal (Ct) residues.…”
Section: Terminology For Proteolytic Pathways That Target N-termini Amentioning
confidence: 99%
“…C, Docking scores of the 20 residues Icl1, Fbp1, and Mdh2 degrons in wild type (red) and (Pro 1 ▶ Ser 1 ) mutated (blue) forms the docking scores (Figure 4), a longer peptide has little influence on the binding affinity. Mdh2 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . Generally, the docking scores and interaction patterns of the three mutated peptides are comparable.…”
Section: N-end Proline Recognitionmentioning
confidence: 99%
“…Second, the ubiquitin is transferred to the E2 conjugating enzyme . Finally, is the ligation of the polyubiquitin to the destabilized protein through its cognate E3 ligase enzyme ( recognin ) in order to be shredded by the ATP‐dependent 26S proteasome . A mammalian genome encodes more than 800 E3 Ub‐ligases which target different degrons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation